Studies on the Chemical Control of Psychrophilic Bacterial Spoilage of fish. ii -The Effect of Antibiotics on the growth of Psychrophilic Bacteria Isolated marine Fish - ANAND, C P; SETTY, T. M RUDRA (Fishery Technology, 2017)
Among the various antibiotics tried, tetracyclines particularly chlorotetracycline(CTC), chloramphenicol and chlorostrep were found to be fairly effect]ve at 8 and 10 p.p.m.levels. The order of sensjtivity to CTC among the six genera studied was found to be Achromobacter< Flavobacterium< Pseudomonas< Micrococcus< Vibrio< Alcaligenes. It was observed that species belonging to Achromobacter, Flavobacterium and Pseudomonas were generally more resistant to antibiotics than species belonging to other genera. Among the resistant organisms, Achromobacter superficialis was found to be most resistant and only CTC at 10 p.p.m. level could partially inhibit this culture. The useful combinations of antibiotics for commercial application are discussed.